La participación docente en la toma de decisiones desde la visión micropolítica - Obando Castillo, Gustavo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2008)
The teacher is the one who experiences close by the problematic of the schoolsystem, the one who makes decisions, modifies or sabotages the school plans, theone who transmits the vision of the school or makes it difficult, among othersaspects; all which reveal the teacher as the key for maintaining alive the educativeorganizations. For this reason, it is important that the teacher participates in theschools with consciousness taking part of the decision making process.However, in a micropolitical context, the participation can occur in a complexway and not always be open to discussion, making use of a variety of strategies(like alliances, rumors and comments) so that the different groups and individualsreach their interests, those that are not necessarily aligned with the school ones orother groups’ interests.

El docente es quien vive de cerca la problemática de la escuela, quien concreta,tergiversa o sabotea los planes de acción, quien transmite la visión institucional ola dificulta, entre otros aspectos; lo cual lo revelan como pieza clave para la vida delas organizaciones educativas. Por ello es importante que participe en las escuelasde forma real, es decir, que intervenga en la toma de decisiones.Sin embargo, en un contexto micropolítico, la participación puede darse demanera compleja y no siempre abierta, empleando una serie de estrategias comoalianzas, rumores y chismes, para que los diversos grupos e individuos alcancensus intereses, los que no necesariamente están alineados con los de la escuela o conlos de los demás grupos.
Keywords: Organización Educativa; Micropolítica; Participación Del Profesor; Toma de Decisiones; Educational Organization; Micropolitics; Teacher Participation; Decision-Making; https://purl.org/pe-repo/ocde/ford#5.03.00